2009
DOI: 10.1155/2009/513874
|View full text |Cite
|
Sign up to set email alerts
|

Extended Spectrumβ-Lactamases among Gram-Negative Bacterial Isolates from Clinical Specimens in Three Major Hospitals in Northern Jordan

Abstract: Background and Objectives. Extended spectrum β-lactamase (ESBL) production is increasing all over the world, and organisms other than E. coli and K. pneumoniae are acquiring this character. ESBL production is detectable by automation, E-test, double disk diffusion (DDD), and PCR. This study aimed to determine the prevalence of ESBL production among clinical isolates of gram-negative rods, and to evaluate the effectiveness of augmentation of clavunate with Cefotaxime, Ceftazoxime, Aztreonam, Ceftriaxone, and Ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
15
1
2

Year Published

2013
2013
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(22 citation statements)
references
References 28 publications
4
15
1
2
Order By: Relevance
“…That study demonstrated a remarkable and worrisome increase in ESBLs producing E. coli isolates (around 30 %) and K. pneumoniae isolates (around 28 %) [13]. Another study from hospitals of Jordan recognized that the prevalence of ESBLs producing E. coli and K. pneumoniae was 10.8 and 34.0 %, respectively [14]. A similar study from Vietnam has also detected ESBLs in 48.1 % of gram-negative bacilli associated IAIs [3].…”
Section: Discussionmentioning
confidence: 98%
“…That study demonstrated a remarkable and worrisome increase in ESBLs producing E. coli isolates (around 30 %) and K. pneumoniae isolates (around 28 %) [13]. Another study from hospitals of Jordan recognized that the prevalence of ESBLs producing E. coli and K. pneumoniae was 10.8 and 34.0 %, respectively [14]. A similar study from Vietnam has also detected ESBLs in 48.1 % of gram-negative bacilli associated IAIs [3].…”
Section: Discussionmentioning
confidence: 98%
“…Subsequently, using the results of testing with cefotaxime, ceftazidime, ceftriaxone, and aztreonam (30 µg of each), β-lactam resistant isolates (ESBL Production) were initially screened out according to [14]. Their presence were then confirmed by the disk approximation test according to [15]. Herein, any augmentation which appear to increase the diameter of the inhibition zone between the central amoxi-clav disk and any of the surrounding disks for the cefotaxime, ceftazidime, ceftriaxone, and aztreonam that was distributed around the amoxi-clav disk was considered as positive for the presence of ESBL Production.…”
Section: Bacterial Characterizationmentioning
confidence: 99%
“…This study found that ESBL-producers isolates were as high as 50.8%, which is comparable with other studies from Jordan 50.3% 37 or Pakistan (54% -57.4%) [38][39][40] , but higher than studies from India (40%) 17 , Tanzania (39.1%) 41 , Iran (21% and 35%) 42,43 , Saudia Arabia (24.5% in children) 44 , Lebanon 17.7% (23.5% from hospitalized children with UTIs and 14.1% from community UTIs), and from other studies in Jordan 10.8%. 45 The prime factors for increasing resistant to 3rd generation cephalosporin or other broad spectrum antibiotics are; the over prescriptions of these antibiotics beside the lack of routine screening for ESBL-producer E.coli or isolation guidelines for the infected patients. 46 38,40,41 ) havebeen also found in different studies.…”
Section: Bacterialisolatesmentioning
confidence: 99%